FasL Is Required for Osseous Healing in Extraction Sockets in Mice - Apaza Alccayhuaman, Karol Alí; Heimel, Patrick; Lee, Jung-Seok; Tangl, Stefan; Strauss, Franz J.; Stähli, Alexandra; Matalová, Eva; Gruber, Reinhard (Frontiers in Immunology, 2021)
Fas ligand (FasL) is a member of the tumor necrosis factor (TNF) superfamily involved in the activation of apoptosis. Assuming that apoptosis is initiated after tooth extraction it is reasonable to suggest that FasL may play a pivotal role in the healing of extraction sockets. Herein, we tested the hypothesis of whether the lack of FasL impairs the healing of extraction sockets. To this end, we extracted upper right incisors of FasL knockout (KO) mice and their wildtype (WT) littermates. After a healing period of two weeks, bone volume over total volume (BV/TV) via µCT and descriptive histological analyses were performed. µCT revealed that BV/TV in the coronal region of the socket amounted to 39.4% in WT and 21.8% in KO, with a significant difference between the groups (p=0.002). Likewise, in the middle region of the socket, BV/TV amounted to 50.3% in WT and 40.8% in KO (p<0.001). In the apical part, however, no difference was noticed. Consistently, WT mice displayed a significantly higher median trabecular thickness and a lower trabecular separation when compared to KO group at the coronal and central region of the socket. There was the overall tendency that in both, female and male mice, FasL affects bone regeneration. Taken together, these findings suggest that FasL deficiency may reduce bone regeneration during the healing process of extraction sockets.